Study of Factors Influencing Vegetative Propagation of Jatropha curcas - Ghosh, Lekha; Singh, Lalji (Indian Forester, 2010)
Different auxin concentrations significantly influenced the rooting in J. curcas. Auxin concentrations of 500 mgl-1 and 1000 mgl-1 IBA showed minimal sprouting and rooting than untreated cuttings. The untreated cuttings yielded 93.50 % and 81.30 % sprouting, 62.60 % and 47.60 % rooting and 15.98 and 11.47 roots/cutting in mist chamber and field, respectively. Cuttings from lower positions gave better (82.00 %) sprouting than middle (75.70 %) and upper (66.60 %) positions. Rooting varied from 35.40 % to 57.20 % for different cutting positions tested. For number of roots/cutting, lower position had highest (10.79) and upper position had lowest (6.84) number of roots. Among the three seasons tested, rainy season gave maximum (7.20 cm) root length while it was lowest (5.19 cm) in winter. Rainy season yielded highest (11.33) root number whereas, winter had lowest (6.36) root number. Rooting was highest (58.90 %) in rainy season and lowest (29.50 %) during winter season. Sprouting was also maximum (91.70 %) in rainy season and minimum (51.30 %) in winter season. J. curcas is easy to root and there is no need to apply auxin (IBA) externally. Without auxin (IBA) treatment, it produced sufficient sprouting and rooting. The study suggests growing thicker cuttings with 14-15 mm diameter in rainy season yields maximum sprouting and rooting.